2020
DOI: 10.3389/fonc.2020.00597
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility and Resistance Mechanisms During Photodynamic Therapy of Melanoma

Abstract: Melanoma is the most aggressive malignant skin tumor and arises from melanocytes. The resistance of melanoma cells to various treatments results in rapid tumor growth and high mortality. As a local therapeutic modality, photodynamic therapy has been successfully applied for clinical treatment of skin diseases. Photodynamic therapy is a relatively new treatment method for various types of malignant tumors in humans and, compared to conventional treatment methods, has fewer side effects, and is more accurate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 193 publications
0
40
0
Order By: Relevance
“…In clinical practice, hypoxia is a major problem in cancer treatment ( 170 ). The current novel photodynamic therapy technology mainly relies on ROS to kill cancer cells, but the hypoxic tumor environment limits its therapeutic value ( 171 , 172 ); thus, combinations with ATV may be a solution. Many studies have also revealed that ATV can indeed improve the efficacy of radiotherapy, chemotherapy, and immunotherapy by reducing the rate of oxygen consumption ( 173 , 174 ).…”
Section: Progress On the Use Of Quinoline Antiparasitic Drugs For Treating Cancermentioning
confidence: 99%
“…In clinical practice, hypoxia is a major problem in cancer treatment ( 170 ). The current novel photodynamic therapy technology mainly relies on ROS to kill cancer cells, but the hypoxic tumor environment limits its therapeutic value ( 171 , 172 ); thus, combinations with ATV may be a solution. Many studies have also revealed that ATV can indeed improve the efficacy of radiotherapy, chemotherapy, and immunotherapy by reducing the rate of oxygen consumption ( 173 , 174 ).…”
Section: Progress On the Use Of Quinoline Antiparasitic Drugs For Treating Cancermentioning
confidence: 99%
“…The results of this study may be considered after further clinical trials in tumor treatment. [34] For aggressive cancers such as melanoma in which chemotherapy and radiotherapy are ineffective, the efficacy of immunoprotective photodynamic therapy (PDT) as an adjuvant in surgery is also being investigated [35], especially since this therapy has been successfully used to treat patients with non-melanoma skin cancer [36], esophageal cancer [37], head and neck cancers [38], breast cancer [39] and lung cancer [40,41]. Towards the development of specialized photosensitizers (PS) for the treatment of pigmented melanomas, nine novel near-infrared (NIR) absorbing photosensitizers based on divalent rubidium compounds have been investigated [35].…”
Section: Photothermal Therapymentioning
confidence: 99%
“…Additionally, technical limitations in PDT are mostly related to the devices through which light can be guided to deep-seated tumors for activating PDT locally. An interesting issue Pharmaceutics 2021, 13, 1032 2 of 25 for further improving PDT is the characterization of the complex mechanisms underlying its therapeutic effects and the potential therapy-induced resistance [4], both aspects being highly dependent on the tumor type, the structure and properties of the PS and on the PDT settings in terms of light wavelength and fluence. Particular aspects characterizing PDT-induced responses in tumor cells have been already documented, connecting the PDT-induced oxidative stress, cell death, survival mechanisms and danger-associated molecular patterns (DAMPs) production and immunity [5][6][7], but a detailed picture of the intra-network connections is still missing.…”
Section: Introductionmentioning
confidence: 99%